Model Peningkatan Kinerja Keuangan melalui Financial Behavior sebagai Variabel Intervening - Andi Iswan; Sabarudin Sabarudin; Neks Triani; Surianto Ilham (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
MSMEs in Kolaka Regency continue to continue their business activities using digitalization even though the pandemic is over. The development of contemporary financial technology (fintech) has made a significant contribution to increasing efficiency and economic value in the buying and selling transaction process and payment systems, while maintaining its effectiveness. Along with the advancement of fintech, competence in digital literacy has also increased its urgency in the current era, as evidenced by the real impact of digitalization on the level of welfare, both at the individual and business entity levels. Business actors who do not have digital capabilities are at risk of being excluded from the various economic benefits offered by digital-based business models. Explicitly, mastery of digital literacy is a basic prerequisite that allows individuals to optimize the various economic prospects available in the modern digital landscape. In this context, financial behavior becomes relevant, covering aspects such as controlling expenses, discipline in fulfilling debt repayment obligations on time, and implementing wise debt and savings management as a basis for financial decision-making. Facing the transition to the post-Covid-19 pandemic era, adaptation through the implementation of digitalization is a must for business continuity.